Tissue features of cattle affected by foot-and-mouth disease - Vionita Alya Sarura; Fieki Hilyah Zamzami (Jurnal Agricultural Science, 2023)
Foot and Mouth Disease (FMD) is perhaps one of the most detrimental diseases in cattle farming. With the aim of understanding the effect of this disease on the body tissues of cattle, this research carried out precise writing research. This study aims to provide a comprehensive picture of changes in body tissue in cows affected by FMD. Writing concentration techniques are used to distinguish, collect, break down and combine important written sources. The data found in this examination comes from logical articles, books, and exploratory reports covering the period 2000 to 2021. Writing views are displayed through logical information bases such as PubMed, Google Researcher, and IEEE Xplore, using appropriate slogans. The results of this study reveal that FMD disease in cattle causes serious histopathological changes in body tissue. The first sores occur on the mouth, lips, and feet, with the development of characteristic vesicles. The component of the spread of FMD infection in the bull group is also concentrated from top to bottom, including through the circulatory system and lymphatic system. This includes the production of antibodies and safe cells that function to fight infection. However, several variables, such as hereditary variation and stress, can influence the severity of disease in dairy cattle. This study assumes that a top-down understanding of body tissue changes in cattle affected by FMD is important for progressing control systems, preventing infection, and further examination efforts. This information also provides input for efforts to maintain the health of dairy cows and the continuity of the livestock industry. This study provides a foundation for a better understanding of FMD in bulls and encourages future exploration of additional interesting immunization improvements and preventive measures.